46.5: Computational Correction Method for Optical Distortion in Eyewear Displays. (4th October 2019) - Xiao, Xue; Zhang, Lin; Lin, Xiao; Hao, Jianying; Zang, Jinliang; Tan, Xiaodi
Abstract : In this paper, we give a brief introduction of eyewear displays for virtual reality (VR) and augmented reality (AR), and present two computational methods that not only can be applied to traditional eyewear displays but systems with asymmetrical and nonlinear distortion as well. The methods combine image segmentation with linear approximation to correct the optical distortion. Through these approaches, pixel‐mapping table for generating pre‐distorted image can be established simply and quickly. The feasibility has been verified by experiments. These distortion correction methods for eyewear displays can achieve a sufficient accuracy, avoid a great deal of numerical calculations and enable real‐time correction.